Distal Transradial Access for Cerebral Digital Subtraction Angiography: A Case Report on Advantages, Limitations, and Practical Insights - Fritz Sumantri Usman; Asep Muhajirin; Evlyne Erlyana Suryawijaya; Gamaliel Wibowo Soetanto (Journal of Neurointervention and Stroke, 2026)
Highlight: dTRA is a safe alternative to TRA with ergonomic benefits in selected anatomy Careful technique is required in dTRA to avoid snuffbox-related complications dTRA enables effective cerebral angiography with fast hemostasis and artery preservation ABSTRACT Introduction: Transradial access (TRA) has showed substantial advantages over transfemoral access (TFA), including decreased morbidity and mortality and increased patient comfort, resulting in its widespread usage. The distal transradial approach (dTRA) offers advantages such as better radial artery preservation, improved ergonomics, and a lower risk of hand ischemia, with early studies reporting high technical success and few complications. In neurointervention, dTRA is emerging as an alternative for cerebral angiography, providing greater patient comfort, fewer access-site complications, and shorter hemostasis times, although evidence remains limited. Case: A 45-year-old man underwent cerebral digital subtraction angiography (DSA) using distal transradial access to further evaluate suspected bilateral middle cerebral artery thrombosis. Conclusion: Appropriate patient selection for dTRA requires careful consideration of both suitability for radial access and anatomical factors, as dTRA may be preferred in certain clinical scenarios, but caution is necessary to avoid injury to surrounding structures in the anatomical snuffbox. For diagnostic cerebral angiography, dTRA demonstrates favorable procedural success with improved safety and patient comfort; however, further studies are required to support its wider application in neurointervention.